Initial development and validation of the Entrepreneurial Orientation Profile Inventory (EOPI) - Smith, Michael Robert (Kansas State University, 2011)
Entrepreneurship represents an important path to job creation, product development and organizational competitive advantage. Therefore, the identification and retention of entrepreneurial talent is of primary importance. The Entrepreneurial Orientation Profile Inventory (EOPI) was developed to evaluate the Proactiveness, Innovativeness and Risk-Taking dimensions of Entrepreneurial Orientation using a situational judgment test (SJT) testing methodology. The current research outlines the initial development of the testing items and provides a preliminary review of the process used to develop a scoring key and evaluate the psychometric properties of the measure among two independent samples. Study 1 focused on developing a key to score and evaluate data in subsequent samples. In Study 1, 49 adult workers provided ratings regarding the most and least effective response to 12 business-related scenarios designed to measure the Proactiveness, Innovativeness and Risk-Taking dimensions of Entrepreneurial Orientation. Interrater consistency analyses were conducted to determine the correct rank order of the response options within the most and least effective response conditions. In the most effective condition, raters reached consensus on the correct ranking of the response options for 7 of the 12 items. In the least effective condition, raters reached consensus on the correct ranking of the response options for 9 of the 12 items. The highest ranked response option was identified as the “correct” response and used as a scoring key in Study 2. This finding suggests individuals are generally better at identifying a single best ineffective solution to a business-related problem, but less effective at identifying a single best effective solution to a business-related problem. Thus, when using an SJT format to evaluate business-related problems, asking respondents to identify the least effective responses is likely to provide better identification of a “correct” response. Items for which the adult sample reached agreement were retained for further examination in Study 2. Study 2 was conducted to evaluate the impact of three response option instruction and scoring methodologies (i.e., “most effective”, least effective” or a combined “most and least effective”) on the reliability and validity of the EOPI measure. Using a sample of 188 undergraduate students, the construct and criterion validity of the EOPI measure as a unidimensional composite and at the item level was evaluated. Across the three conditions, the results of the construct and criterion validity analyses generally failed to support the EOPI instrument as an effective method to evaluate Entrepreneurial Orientation at the composite level. The modest correlation coefficients among the criteria variables suggest a potentially broader measurement issue with currently available measures of Entrepreneurship in general. Within the “least effective” response instruction condition, minor significant results were found at the item level. A review of these items provides insight into how modifications of EOPI items may facilitate future item development. Further, the current research also suggests that biographical data may provide insight into the measurement of Entrepreneurial Orientation. A biodata-based unidimensional composite of Entrepreneurial Behavior was found to be both marginally reliable and significantly related to an alternative measure of Entrepreneurial Orientation. The development of additional biodata items that correlate with the current items is likely to improve the psychometric properties of the Entrepreneurial Orientation composite and provide insight into the role of previous experience as a valid and reliable indicator of Entrepreneurial Orientation and Entrepreneurship behaviors.
Keywords: Entrepreneurial Orientation; Situational Judgment Test; Psychology (0621)